To Assess Awareness Regarding Child Abuse and Neglect , amongst Emergency Medical Professionals in Pune, India – A Pilot Sludy (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Violence against children is widespread and affects millions of children globally. Violenceagainst children occurs in various forms including physical violence, maltreatment, bullying, emotional orpsychological violence, forced and bonded labour, and trafficking.To prevent child abuse, it is essential that a high degree of awareness is essential amongst all stakeholdersincluding parents, educators and medical professionals. The common thread among all studies conducted inmedical professionals is the lack of focused training and sensitisation that can enhance the ability to detectsuch cases and respond to them promptlyObjective: To Assess Awareness Regarding Child Abuse and Neglect among Emergency MedicalProfessionals in PuneMethodology: As part of an awareness initiative by the Institute, an online session was conducted for theEmergency Medical Professionals (EMP) in Pune city. 65 Emergency Medical Professionals working invarious hospitals located around all parts of Pune participated in the session. After the session was completed,informed consent was taken from the participants for answering a questionnaire based on the subject.The questionnaire chosen for the study was Child Abuse and Neglect Awareness Scale (CANA-S) a pretestedand validated tool. The CANA-S tool comprises 4 sections, each section comprising a subscale dedicatedto one of the major categories of child abuse and neglect i.e. physical abuse, sexual abuse, emotional abuse,and neglect.Conclusion: Though the overall awareness about Child Abuse and Neglect is satisfactory, further trainingprograms should be encouraged, to achieve near 100 % awareness amongst EMS professionals in order toprevent and report every single case of Child Abuse and Neglect.
Keywords: Child abuse, awareness, sexual abuse